Freies Land - Alvart, Christian; Kamml, Siegfried (Deutschland: Goethe- Institute e.V., 2021)
1992 im ostedeutschen Grenzland, kurz nach der Wiedervereinigung: Neben der Hoffnung auf eine bessere Zukunft macht sich auch grosse Enttaeuschung breit. Zwei minderjaehrige Schwestern sind spurlos verschwunden. Scheinbar stoert kaum jemanden, dass die beiden weg sind. Wohl in den Westen abgehauen, meinen die Nachbarn. Die Kommissare Stein und Bach stossen auf Schweigen. Trotzdem finden sie heraus, dass auch schon frueher Maedchen verschwunden sind. Als dann die Leichen der beiden Maedchen auftauchen, beginnen sie zu ahnen, dass sie es mit einer grausamen Mordserie zu tun haben.
[EN] In the winter of 1992, little of the blooming landscapes promised by Helmut Kohl are to be seen in the remote region of northeast Germany where the two investigators, Bach and Stein, have been sent. Two girls have disappeared. It is rumoured that they simply left for the West, but little of what is said sounds all that credible. A short time later, two horribly mutilated bodies are found, and then it comes out that the two girls are not the first young women of the village to disappear without a trace. The dissimilar investigators dig deeper and deeper into the meshwork of lies told by the locals. Bach, who knows every trick in the book, also has to deal with his thorny past as a former piece of the GDR's executive apparatus gradually coming to light, while Stein, who is noticeably less emotionally stable than his shrewd partner, has seemingly left the apparently alien and distant city of Hamburg for a country with its own laws.
Keywords: Violence; Fall of the Wall / Reunification; GDR; Thriller / Action / Kriminalfilm